Binding specificity of anti-HNK-1 IgM M-protein in anti-MAG neuropathy: Possible clinical relevance. (February 2015) - Hamada, Yukihiro; Hirano, Makito; Kuwahara, Motoi; Samukawa, Makoto; Takada, Kazuo; Morise, Jyoji; Yabuno, Keiko; Oka, Shogo; Kusunoki, Susumu
Highlights: Anti-myelin-associated-glycoprotein (MAG) neuropathy was studied. An ELISA method was established to test binding specificities of anti-MAG antibody. We found the distinct binding specificities of anti-MAG antibody in 19 patients. Our result suggested a possible clinical relevance of the binding specificities. Abstract: Anti-myelin-associated-glycoprotein (MAG) neuropathy is an intractable autoimmune polyneuropathy. The antigenic region of MAG is the human natural killer-1 (HNK-1) carbohydrate. We and others previously suggested that the extension of antibody reactivities to HNK-1-bearing proteins other than MAG was associated with treatment resistance, without statistical analyses. In this study, we established an ELISA method with recombinant proteins to test binding specificities of currently available monoclonal antibodies to MAG and another HNK-1-bearing protein, phosphacan. Using this system, we found the distinct binding specificities of anti-MAG antibody in 19 patients with anti-MAG neuropathy. Their clinical relevance was then determined retrospectively with the adjusted 10-points INCAT disability score (0 = normal and 10 = highly disable). The results showed that strong reactivities of anti-MAG antibodies to phosphacan were significantly associated with treatment resistance or progressive clinical courses, indicating a possible clinical relevance of the binding specificities.